Evaluation of Quality of Service on Megavision Internet Services Provider in Jelekong Village Using Speedtest by Ookla - Rusdan, Muchamad (Journal of Informatics and Communication Technology (JICT), 2024)
This research aims to test the Quality of Service (QoS) on the internet service provider Megavision in Jelekong Village, Baleendah District, Bandung Regency using Speedtest by Ookla Mobile. Measurement methods include download speed, upload speed, throughput, latency (ping), jitter, and packet loss. The research results show that the Megavision Provider can provide relatively good quality internet services, with an average download speed of 19.10 Mbps, an average upload speed of 19.78 Mbps, average throughput of 38.886 kbps in the "Good" category, average latency of 52.78 ms in the "Very Good" category, average jitter of 17.33 ms in the "Good" category, and average packet loss of 1.25% in the "Very Good" category based on the TIPHON standard. Although performance variations occur, especially during peak hours during the day, the test results generally show the stability and reliability of Provider Megavision's internet service. The results of this research can be used as a basis for carrying out continuous monitoring and improving infrastructure and service quality to provide a more satisfying user experience in Jelekong Village